2005
DOI: 10.1002/uog.1834
|View full text |Cite
|
Sign up to set email alerts
|

Improved first‐trimester Down syndrome screening performance by lowering the false‐positive rate: a prospective study of 9941 low‐risk women

Abstract: K E Y W O R D S:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 40 publications
4
38
2
1
Order By: Relevance
“…The detection rate for Turner syndrome in our study was 80% (8/10) as compared with 100% (5/5) reported by Wojdemann et al. [10] Other chromosome anomalies include translocation, microdeletion and mosaics and show a combined detection rate of 63.1% (12/19), which is slightly higher than that reported by Krantz et al. (40% including a total of 45 advanced age and younger women) [17].…”
Section: Commentscontrasting
confidence: 66%
“…The detection rate for Turner syndrome in our study was 80% (8/10) as compared with 100% (5/5) reported by Wojdemann et al. [10] Other chromosome anomalies include translocation, microdeletion and mosaics and show a combined detection rate of 63.1% (12/19), which is slightly higher than that reported by Krantz et al. (40% including a total of 45 advanced age and younger women) [17].…”
Section: Commentscontrasting
confidence: 66%
“…This is in accordance with reports from the Copenhagen First Trimester Study. 7 clearly illustrates the rationale in screening using a combined risk assessment in the first trimester. As expected, this strategy reduces the number of unnecessary diagnostic procedures.…”
Section: Discussionmentioning
confidence: 98%
“…This was certainly the case in and around Copenhagen, when a prospective study of around 10 000 women was done in 1998-2001. 7 Nuchal translucency scanning was introduced in some departments even before the national guidelines were changed.…”
Section: Discussionmentioning
confidence: 99%
“…Combining these three screening markers (fβ-hCG, PAPP-A and NT) with maternal age, using a risk calculation method similar to that of the triple test, originated the 'first trimester combined test' (Wald and Hackshaw, 1997). Over the years, numerous studies have been published showing that with the first trimester combined test approximately 85-90% of all DS cases could be detected at a 5% FPR (Jaques et al, 2007, Nicolaides et al, 2005, Spencer and Nicolaides, 2003, Valinen et al, 2007, Wojdemann et al, 2005. Under strict guidelines issued by the Dutch Centre for Population Research the firsttrimester screening policy for DS was fully implemented in the Netherlands as of January 1, 2007.…”
Section: Prenatal Screening For Down Syndromementioning
confidence: 99%